2015
DOI: 10.1002/cncr.29579
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of copy number alterations in adolescent and adult patients with precursor B acute lymphoblastic leukemia enrolled in PETHEMA protocols

Abstract: ; for the Spanish PETHEMA Group and the Spanish Society of Hematology BACKGROUND: Some copy number alterations (CNAs) have independent prognostic significance for adults with acute lymphoblastic leukemia (ALL). METHODS: This study analyzed via multiplex ligation-dependent probe amplification the frequency and prognostic impact of CNAs of 12 genetic regions in 142 adolescents and adults with de novo precursor B-cell ALL. RESULTS: The cyclindependent kinase inhibitor 2A/B (CDKN2A/B) deletion (59 of 142 or 42%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
3
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 31 publications
9
33
3
4
Order By: Relevance
“…In the present study, IKZF1 gene deletions were predominant, followed by CDKN2A/2B deletions. Ribera et al (15) reported that German adolescents and adult patients with ALL exhibited prevalent deletions of CDKN2A/2B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, IKZF1 gene deletions were predominant, followed by CDKN2A/2B deletions. Ribera et al (15) reported that German adolescents and adult patients with ALL exhibited prevalent deletions of CDKN2A/2B.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of patients with a better prognosis was 1, 5, and 0%, respectively. Ribera et al (15) reported that the 5-year cumulative incidence rate (CIR) was higher and that the OS was poorer in patients with IKZF1 deletion than in those without the deletion. Additionally, CDKN2A/2B deficiency in patients with B-ALL was associated with a poor OS.…”
Section: Discussionmentioning
confidence: 99%
“…Biallelic deletions of CDKN2A/B were observed in 9 of 12 cases, more com-monly among adolescent and adult BCR-ABL1 -negative patients. Nevertheless, deletions of CDKN2A/B are associated with poor outcome [Moorman et al, 2014;Ribera et al, 2015], and aCGH analysis provides more accurate results, since it has the ability to identify deletions <190 kb in size, which therefore are undetectable by a commercially available p16 (CDKN2A) FISH probe.…”
Section: Discussionmentioning
confidence: 99%
“…5 PETHEMA high-risk (HR) BCP ALL was defined as those patients older than 30 years, with hyperleukocytosis over 30 × 10 9 /L or patients with MLL/KMT2A rearrangements at presentation. 5 PETHEMA high-risk (HR) BCP ALL was defined as those patients older than 30 years, with hyperleukocytosis over 30 × 10 9 /L or patients with MLL/KMT2A rearrangements at presentation.…”
Section: Methodsmentioning
confidence: 99%